2012
DOI: 10.3389/fphys.2012.00346
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell derived cardiomyocytes as models for cardiac arrhythmias

Abstract: Cardiac arrhythmias are a major cause of morbidity and mortality. In younger patients, the majority of sudden cardiac deaths have an underlying Mendelian genetic cause. Over the last 15 years, enormous progress has been made in identifying the distinct clinical phenotypes and in studying the basic cellular and genetic mechanisms associated with the primary Mendelian (monogenic) arrhythmia syndromes. Investigation of the electrophysiological consequences of an ion channel mutation is ideally done in the native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 85 publications
(218 reference statements)
7
150
2
Order By: Relevance
“…Even though Ca 2 + ‐handling features appear conserved in independent hiPSC‐CM cultures from different research groups (Hwang et al , 2015a, 2015b; Kane and Terracciano, 2015), heterogeneity has been widely observed in other electrophysiological properties such as the APD (Figure 3), upstroke velocity and current densities (Hoekstra et al , 2012). Inconsistent results on the mechanism of hiPSC‐CM automaticity have also been noted: Kim et al reported a Ca 2 + clock mechanism, consistent with ivabradine having no effect on beating frequency (Kim et al , 2015).…”
Section: Limitations In Applicability Of Hipsc‐cm To Large‐scale Drugmentioning
confidence: 99%
“…Even though Ca 2 + ‐handling features appear conserved in independent hiPSC‐CM cultures from different research groups (Hwang et al , 2015a, 2015b; Kane and Terracciano, 2015), heterogeneity has been widely observed in other electrophysiological properties such as the APD (Figure 3), upstroke velocity and current densities (Hoekstra et al , 2012). Inconsistent results on the mechanism of hiPSC‐CM automaticity have also been noted: Kim et al reported a Ca 2 + clock mechanism, consistent with ivabradine having no effect on beating frequency (Kim et al , 2015).…”
Section: Limitations In Applicability Of Hipsc‐cm To Large‐scale Drugmentioning
confidence: 99%
“…Of note, however, the literature reports a wide range of values in the basic electrophysiological properties of hiPSC‐CMs, action potentials differing an order of magnitude and beating rates anywhere between 0.5 and 1.5 Hz, but also specific ion currents (e.g. the slow I Ks , and the rapid I Kr components of the delayed rectifier potassium currents, the sodium current I Na , and the L‐type calcium current I CaL ) varying widely even among wild‐type control hiPSC‐CMs 55, 56. Most notably, very different levels of I Ks have been described (ranging from ~ 0.3 to ~ 2.5 pA/pF 5, 57), variable observation leading to controversial conclusions: on the one hand, I Ks recapitulates physiological behaviour in playing a major role when repolarisation reserve is attenuated 58, 59; on the other, it seems to contribute to repolarisation in hiPSC‐CMs even in the absence of sympathetic stimulation 5, 36, 60, 61.…”
Section: Pathological Phenotypes and New Mechanistic Insightsmentioning
confidence: 99%
“…A detailed discussion of protocols and potential pitfalls in the production and use of human iPSCs is beyond the scope of this article but has been the subject of recent reviews and editorials Yamanaka, 2010, 2011;Mummery, 2011;Xu et al, 2011;Sinnecker et al, 2012). With respect to the specific issue of electrophysiologic characteristics of these cells, there also have been several recent reviews (Poon et al, 2011;Hoekstra et al, 2012;Zeevi-Levin et al, 2012). In the following discussion, we focus specifically on reports concerning aspects of automaticity and the presence of nodal-like cells in these preparations since that is most relevant to the current topic.…”
Section: B Human Induced Pluripotent Stem Cells and Automaticitymentioning
confidence: 99%